Strategies to Improve Employees' Work Efficiency in One Brance of ABC Thai Restaurant - Zheng, ShuYue; Fernando, Maria Socorro C.L. (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
This study focuses on determining the factors that influence work efficiency in a Thai Restaurant and aims to design strategies to improve employee work efficiency in the workplace. Mixed-method research using qualitative interviews and a quantitative questionnaire was utilized in this study. There were 12 interview respondents from the top management and middle management and 82 respondents for the questionnaire survey. Based on the qualitative analysis from inter-coding, the restaurant should give employees a clear goal and schedule to follow and choose a good leader to improve teamwork. The quantitative results from descriptive and inferential statistical analysis showed the organization needed to improve work efficiency by strengthening teamwork and employee development, such as teamwork training programs and employee development workshops.